Collective experiences in medical music therapy teams during COVID-19. Issue 3 (27th May 2022) - Shoemark, Helen; Bates, Debbie; Collier, Elizabeth; Hannan, Ann; Harman, Elizabeth; Kennelly, Jeanette; Knott, David; Thomas, Amy; Troyano, Amy P.
ABSTRACT: Introduction: During the COVID-19 pandemic music therapy managers in hospitals were responsible for supporting their teams through relentless planning and implementation of change, including working virtually and in–person. The Creative Arts Therapies Managers' Network was established as a group of eight music therapy managers to formulate and appraise thinking and generate and refine meaningful constructs to sustain their own capacities as managers. Method: Weekly meetings for the period April to July 2020 were recorded, transcribed and analyzed to generate themes that reflected these managers' early pandemic experiences. Results: Each manager used these themes as a basis for reflection to write stories that represented their lived experiences in that period. Discussion: These stories are discussed using theoretical constructs which inform them, including aspects of identity, moral dilemmas, relentless uncertainty, and resilience in response to uncertainty. These stories and underpinning considerations illuminate previously unexplored experiences of music therapy managers in hospitals.